Digital Training Components and Civil Servants’ Digital Productivity: The Mediating Role of Adaptive Competence - Wulan Sari; Euis Mufahamah; Harold Kevin Alfredo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Digital transformation in the public sector encourages civil servants to utilize technology not only for administrative purposes but also to improve efficiency, accuracy, and work performance. This study examines the influence of Intelligent Learning-Based Training and Digital Training Components on the Digital Productivity of civil servants at the Bureau of Economic Affairs of the Regional Secretariat of Lampung Province, with Adaptive Competence serving as a mediating variable. A quantitative approach with a non-experimental survey design was applied, and data were collected through structured questionnaires distributed to employees engaged in digital-based work activities. The data were analyzed using structural model testing procedures. The findings reveal that Intelligent Learning-Based Training does not significantly influence Adaptive Competence or Digital Productivity. Conversely, Digital Training Components positively and significantly affect both Adaptive Competence and Digital Productivity. Adaptive Competence also has a positive impact on Digital Productivity and mediates the relationship between Digital Training Components and Digital Productivity. However, Adaptive Competence does not mediate the relationship between Intelligent Learning-Based Training and Digital Productivity. These results indicate that civil servants’ digital productivity is more effectively improved through practical, relevant, accessible, and well-evaluated digital training programs than through intelligent learning systems alone. Therefore, public institutions are encouraged to develop digital training initiatives that align with employees’ daily work demands while strengthening their adaptive competence in responding to technological changes.